Splenic macrophages in preterm infants: a necropsy study. Issue 5 (May 1996) - Variend, S; Drummond, A; Coombs, R
Abstract : AIMS: To study the frequency and nature of histiocytes in the splenic red pulp of infants who died following complicated immaturity/prematurity. METHODS: Twenty four preterm/immature infants were investigated. Frozen sections of formalin fixed splenic tissue were stained with Oil Red O. Paraffin wax sections from the same tissue were conventionally stained with haematoxylin and eosin. Immunohistochemistry was carried out for a number of macrophage markers. The administration of Intralipid was compared with the presence and extent of tissue macrophages. RESULTS: The spleens of 10 infants showed varying degrees of Oil Red O positivity ranging from mild to strong. In all these cases varying numbers of macrophages were confirmed in the splenic parenchyma in ordinary sections. The immunomarkers indicated that the histiocytes belonged to the macrophage phagocytic system. Of the 10 cases with splenic macrophages all had received Intralipid. Of those not receiving Intralipid none showed splenic macrophages. Seven had received Intralipid but did not have splenic macrophages; they had either only received small amounts of Intralipid or Intralipid was discontinued before death. CONCLUSIONS: Splenic macrophages are common at necropsy in immature/preterm infants. The macrophages are most lucidly demonstrated using Oil Red O staining in frozen sections. There is a strong association between the presence of splenic macrophages and Intralipid administration.